Grammatik der Menschenbezeichner in biographischen Kontexten - Geierhos, Michaela

Informationsextraktion aus Stellenanzeigen im Internet - Bsiri, Sandra; Geierhos, Michaela (LWA 2007: Lernen - Wissen - Adaption, Halle, September 2007, Workshop Proceedings)
Dieser Beitrag beschäftigt sich mit der Informationsextraktion aus Stellenanzeigen im französischsprachigen Web. Ziel dieser Arbeit ist es, unstrukturierte Dokumente in Repräasentationsvektoren anhand lokaler Grammatiken zu transformieren. Auf diese Weise wird es möglich, den Stellenmarkt für Jobsuchmaschinen transparenter zu gestalten, indem nur auf dem Inhalt der Anzeige in Form von Darstellungsvektoren anstatt auf unübersichtlichem Fließtext gesucht werden muss.

The valency of experiential and evaluative adjectives - Mindt, Ilka (Valency. Theoretical, Descriptive and Cognitive Issues)

Constructing an Emblematic Northern Space. The New Brighton Photographs of Martin Parr and Tom Wood - Tönnies, Merle (Spatial Practices 2)

Introduction to the Study of British Culture - Tönnies, Merle; Voigt, Ulrich

London-Diversity and Myth - Tönnies, Merle (Viewfinder Special. Lese-und Arbeitsbuch für die gymnasiale Oberstufe)

Book review: Katharina Uhsadel (2005). Antonia Byatts Quartet in der Tradition des Englischen Bildungsromans. Heidelberg: Winter - Mildorf, Jarmila (Anglistik)

Storying Domestic Violence: Constructions and Stereotypes of Abuse in the Discourse of General Practitioners - Mildorf, Jarmila

Mad Intertextuality: 'Jane Eyre', 'Wide Sargasso Sea', 'After Mrs Rochester' - Mildorf, Jarmila (A Breath of Fresh Eyre: Intertextual and Intermedial Reworkings of 'Jane Eyre')

Das Paradigma des Pikaresken - The Paradigm of the Picaresque

Thinking Northern: Textures of Identity in the North of England

Stierstorfer, K. / L. Volkmann (Hg.): Kulturwissenschaft Interdisziplinär - Tönnies, Merle (Anglistik. International Journal of English Studies)

Distributional data and grammatical structures: The case of so- called subject extraposition - Mindt, Ilka (Zeitschrift für Anglistik und Amerikanistik 54.2, Special issue on "The scope and Limits of Corpus Linguistics – Empiricism in the Description and Analysis of English)

Forms and Functions of Violence in Contemporary Black British Drama - Tönnies, Merle (Anglistentag 2005)

Foregrounding Boundary Zones. Martin Parr's Photographic (De-)Constructions of Englishness - Tönnies, Merle (Spatial Practices 1)

Percy Mtwa, Mbongeni Ngema and Barney Simon: Woza Albert! (1981) - Tönnies, Merle (Drama II)

New Labour in the New Millenium. A Further Theatricalisation of Politics? - Tönnies, Merle (Passauer Arbeiten zur Literatur-und Kulturwissenschaft)

Radicalising Postmodern Biofictions. British Fictional Autobiography of the Twenty-First Century - Tönnies, Merle (Salzburg Studies in English Literature and Culture)

A Midsummer Night's Dream - Tönnies, Merle (Stauffenburg Handbücher)

Boehmer, E.: Stories of Women, 2005 - Tönnies, Merle (Archiv für das Studium der neueren Sprachen und Literaturen)